To prestige care work in home care services - Moreno Colom, Sara (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
The aim of the article is to analyze to role of public administration to the professionalization of care work. It presents the case study carried out on the new management model of the Home Care Service promoted by the Barcelona City Council within the framework of the Superilles Socials project. The hypothesis points out that, unlike the traditional model, this proposal based on the organization of self-managed and territorially limited teamwork entails material and symbolic improvements for employees and users. As a conclusion, the article suggests it isn’t necessary to define new professions related to the social care because is better to prestige the home care workers by new management models from the public administration.